THE FOOD, FEEDING AND REPRODUCTION OF THE BORNEO MULLET, LIZA MACROLEPIS (SMITH), IN A COASTAL ESTUARY IN SRI LANKA - Wijeyaratne, M J S; Costa, H H (Indian Journal of Fisheries, 2011)
Liza macrolepis in Negombo lagoon was found to have two spawning periods, one during January-February and the other during August-September. The males were more abundant in smaller size groups, but attained 1 : 1 sex ratio with growth. The mean lengths at maturity for males and females were 16 and 21 cm respectively. The absolute fecundity was estimated to be 12300-955000 for fish ranging in total" length from 16 cm to 30 cm. The food consisted mainly of polychaetes and detritus. Analysis showed a high similarity between the diets of different size groups.